DAMPAK MAKAN BERGIZI GRATIS TERHADAP MINAT BELAJAR SISWA KELAS 5 SD - Puspa, Riyani; Sarifah, Iva; Yunus, Mahmud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Free Nutritious Meal Program (MBG) is a strategic initiative that aims to improvethe nutritional quality and learning motivation of students in Indonesia. The programis based on data showing that 41% of students in Indonesia experience hunger whilestudying, which negatively impacts their concentration and academic performance.The MBG not only targets school children, but has also been expanded to includetoddlers, pregnant women, and nursing mothers. The government has allocated abudget of IDR71 trillion in the 2025 Draft State Budget for the initial phase of thisprogram, which is planned to begin on January 2, 2025. Interest is a tendency orgreat desire for something, evidenced through giving attention to the subject ofinterest. The Free Nutritious Meal Program (MBG) is one of the flagship initiativeslaunched by President Prabowo Subianto's administration. The main objective ofthe program is to address nutrition issues as well as improve the quality of humanresources in Indonesia, with a special focus on children and pregnant women. It isalso a school meal distribution plan that is expected to provide equity in educationas all students have the opportunity to eat nutritious meals for free. Since itsannouncement, the implementation plan of this program has undergone variousdevelopments. Of course, this will later have an impact on student learningoutcomes. In this study or Research we use the method.